(untitled) (Journal of Hama University, 2024)
The phenomenon of fragmentation of agricultural holdings is one of the distinguishing features of the agricultural sector in Syria, and small and medium farms are the most prevalent in it, and their number has increased as a result of the high population growth rate, which has led to an increase in population pressure on agricultural lands. The study was conducted in Lattakia Governorate on a random sample that included 384 holders In 24 villages, the phenomenon of fragmentation of agricultural holdings was identified. It aimed to study the reality of the phenomenon of fragmentation of agricultural holdings, identify its causes, and the holding capacity, and study the fairness of the distribution of holdings in the coastal plains and mountainous highlands in Lattakia Governorate. The most important results of the study were as follows:1-The degree of fragmentation of holdings in the coastal plains ranged between 0.021118 -0.045667, and ranged from 0.005321 -0.074513 in the mountainous highlands, and the Gini coefficient was about 0.41 in the coastal plains, and 0.35 in the mountainous highlands. This is evidence of inequality in the distribution of holdings.2-There are no statistically significant differences at the level (0.05 ≥ α) for the impact of social factors (increase in the number of family members and inheritance) on the fragmentation of agricultural holdings, because the customs and traditions of encouraging reproduction are the same in the two study areas. 3-There are no statistically significant differences at the level (0.05 ≥ α) for the impact of economic factors (selling and renting land and its insufficiency as a source of livelihood) on the fragmentation of agricultural holdings, due to the similarity of the economic situation in the two study areas, and that the reason for selling land is financial need.